Pengaruh Model Pembelajaran Scramble Berbantuan Media Poster Terhadap Hasil Belajar Siswa Kelas VIII SMP Katolik Anda Luri Waingapu - Agustinus Jongu; Vidriana Oktoviana Bano (Universitas Nusantara PGRI Kediri, 2023)
The problem of this research is the implementation of learning that is still conventional, minimal variations in learning models, causing students to become bored and low learning outcomes. One of the problem solving is done through the use of the scramble learning model assisted by poster media. The aim of this study was to determine the effect of the poster-assisted scramble learning model on student learning outcomes at Andaluri Waingapu Catholic Middle School. This type of research is a quasi-experimental research design using nonequivalent control group design, with a quantitative approach. The research sample was 28 VIIIa students as the control class and 28 VIIIc students as the experimental class. Data collection techniques pretest, posttest, interviews. The results showed that the average value of the experimental class was 78.93, which was greater than that of the control class, 63.21. The results of the paired sample t test posttest data for the experimental class obtained a sig (2-tailed) value of 0.000 <0.05, concluding that the scramble learning model assisted by poster media had an effect on student learning outcomes in class VIII on the material Structure and Function of Plants at Andaluri Catholic Middle School Waingapu.